Diagnostic Criteria of Pediatric Intestinal Myopathies. Issue 3 (March 2018) - Lombardi, Laura; Bruder, Elisabeth; Pio, Luca; Nozza, Paolo; Thai, Elena; Lerone, Margherita; Del Rossi, Carmine; Mattioli, Girolamo; Silini, Enrico Maria; Paraboschi, Irene; Martucciello, Giuseppe
Abstract : ABSTRACT: The authors aim to identify criteria for the diagnosis of intestinal visceral myopathy (IVM); results were compared with ultrastructural studies. Six IVM patients and 7 pediatric control cases (without gastrointestinal diseases) were studied. One case was a typical megacystis-microcolon-intestinal hypoperistalsis syndrome. The diagnostic path included: rectal suction biopsy, one-trocar transumbilical laparoscopic intestinal full-thickness biopsy technique. Pathological analysis included anti-alpha smooth muscle actin staining, and US study of intestinal biopsies. IVM histological examination demonstrated thinning of longitudinal muscle layer. The ratio of circular/longitudinal thickness was evaluated in all samples; in cases, this ratio presented as a mean value of 2.91, and in controls, a mean value of 1.472 ( P = 0.0002). Ultrastructural diagnosis revealed variable myofibrils density in smooth muscle cells, irregularity of sarcolemma membranes, interstitial fibrosis, and myofiber disarray. The authors concluded that in IVM, circular/longitudinal thickness ratio and alpha smooth muscle actin staining can be used as significant tools to address the diagnosis.